2015
DOI: 10.1371/journal.pone.0131444
|View full text |Cite|
|
Sign up to set email alerts
|

Defining the Roles of IFN-γ and IL-17A in Inflammation and Protection against Helicobacter pylori Infection

Abstract: CD4+ T cells have been shown to be essential for vaccine-induced protection against Helicobacter pylori infection. However, the effector mechanisms leading to reductions in the gastric bacterial loads of vaccinated mice remain unclear. We have investigated the function of IFN-γ and IL-17A for vaccine-induced protection and inflammation (gastritis) using IFN-γ-gene-knockout (IFN-γ-/-) mice, after sublingual or intragastric immunization with H. pylori lysate antigens and cholera toxin. Bacteria were enumerated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Indeed, we have observed a significantly higher frequency of IL‐17A + cells in the stomach after infection with H pylori in sublingually immunized mice compared with intragastrically immunized mice . We also observed an increase in frequency of CD11b + Ly6G − inflammatory monocytes in the circulation after vaccination particularly after IG route of immunization in accordance with the study by Moyat et al Furthermore, we have previously reported the dependence of IFNγ on the protective immune response after IG immunization, and thus, the CD11b + Ly6G‐ inflammatory monocytes activated after IG route of vaccination might play a role in the polarization of the CD4 + T‐cell response to a Th1 phenotype . Finally, we saw a decrease in frequency of eosinophils in circulation after vaccination possibly due to their migration to the effector tissues.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, we have observed a significantly higher frequency of IL‐17A + cells in the stomach after infection with H pylori in sublingually immunized mice compared with intragastrically immunized mice . We also observed an increase in frequency of CD11b + Ly6G − inflammatory monocytes in the circulation after vaccination particularly after IG route of immunization in accordance with the study by Moyat et al Furthermore, we have previously reported the dependence of IFNγ on the protective immune response after IG immunization, and thus, the CD11b + Ly6G‐ inflammatory monocytes activated after IG route of vaccination might play a role in the polarization of the CD4 + T‐cell response to a Th1 phenotype . Finally, we saw a decrease in frequency of eosinophils in circulation after vaccination possibly due to their migration to the effector tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Spleens from mice were collected after the sacrifice, and single‐cell suspensions were prepared and cultured . In short, cells were plated (2 × 10 5 cells per well) in the presence or absence of boiled H pylori strain Hel 305 lysate antigens (0.1 and 1 μg/mL) in complete Iscoves modified Dulbecco medium supplemented with supplemented with 10% heat‐inactivated fetal calf serum (Sigma), 50 µmol/L 2‐mercaptoethanol (Sigma), 1 mmol/L l ‐glutamine (Biochrome), and 50 µg/mL gentamicin (Sigma) and incubated for 72 hours at 37°C in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies in the H. pylori immunization model have shown that the sublingual route of immunization is dose sparing for the vaccine antigen and adjuvant compared with immunization via the intragastric route . We now report that, in vitro , when DCs isolated from the CLN or MLN are pulsed with H. pylori antigens and CT and dmLT adjuvants, they are able to effectively activate H. pylori ‐specific CD4 + T cells and induce their cytokine secretion.…”
Section: Introductionmentioning
confidence: 75%
“…(IFN-␥) and interleukin-17 (IL-17) and regulatory T (Treg) cell development, impact the pathology elicited in response to H. pylori colonization (13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%